2000
DOI: 10.1016/s0002-9440(10)64552-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Clusterin in Human Breast Carcinoma

Abstract: Clusterin has been implicated in numerous processes including active cell death, immune regulation, cell adhesion and morphological transformation. The purpose of this study was to examine clusterin expression in a large series of breast carcinomas by immunohistochemistry and in situ hybridization. The study included 40 samples of non-neoplastic glandular epithelia, 42 benign lesions, 15 atypical intraductal hyperplasias, 35 carcinomas in situ, 114 invasive carcinomas, and lymph node metastases from 40 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
187
4
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(214 citation statements)
references
References 18 publications
19
187
4
4
Order By: Relevance
“…For instance, introduction of the clusterin gene into renal carcinoma cells resulted in enhanced formation of metastatic nodules in vivo (Miyake et al, 2002). In addition, the expression level of clusterin was contrastive in breast cancer, where normal breast epithelial cells were always negative for CLU expression (Redondo et al, 2000). A similar expression pattern was observed in our recent study on ovarian carcinoma (Xie et al, 2005).…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, introduction of the clusterin gene into renal carcinoma cells resulted in enhanced formation of metastatic nodules in vivo (Miyake et al, 2002). In addition, the expression level of clusterin was contrastive in breast cancer, where normal breast epithelial cells were always negative for CLU expression (Redondo et al, 2000). A similar expression pattern was observed in our recent study on ovarian carcinoma (Xie et al, 2005).…”
Section: Introductionsupporting
confidence: 79%
“…Although the precise function of CLU remains debatable, a growing body of evidence suggests that overexpression of this protein is implicated in tumorigenesis and metastasis (Steinberg et al, 1997;Redondo et al, 2000;Miyake et al, 2002;Chen et al, 2003;Xie et al, 2005). In a recent study, using a mouse model with Pten conditional prostate deletion, Wang et al (2003) reported that increased CLU expression was found in mutant mouse prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In prostate cancer, sCLU expression was associated with the development of androgen resistance and it (sCLU) is thought to act as a protective agent against treatment-induced cell death. 8,38 In fact, not many studies showed a decrease in sCLU in tumours like that of a proapoptotic. A few reports do, however, suggest decreased sCLU levels in specific cancers, including nonmelanoma skin cancer, 40 oesophageal squamous cell carcinoma, 41 neuroblastoma, 22 prostate, 11,37 and pancreatic cancer 42 (Table 1).…”
Section: Expression Of Clu In Malignant Tumours and Its Potential Rolmentioning
confidence: 99%
“…For example, sCLU was reported to be a prognostic indicator in tumorigenesis and progression of human breast carcinoma. 38 Furthermore, sCLU has been proposed to be a potentially new prognostic and predictive marker for colon carcinoma aggressiveness, since overexpression of sCLU is reported or observed in highly aggressive tumours as well as metastatic nodules. 3 In addition, in prostate LNCaP cells, CLU appeared to be associated with tumour progression and resistant to chemotherapy treatments in vivo.…”
Section: Expression Of Clu In Malignant Tumours and Its Potential Rolmentioning
confidence: 99%